A New Cytotoxic Stilbenoid from Arundina graminifolia - Meng, Chun-Yang; Niu, De-Yun; Li, Yin-Ke; Zhou, Bin; Ye, Yan-Qing; Du, Gang; Hu, Qiu-Fen; Gao, Xue-Mei (Asian Journal of Chemistry, 2014)
A new stilbenoid, gramniphenol K (1) was isolated from Arundina graminifolia. Its structure was elucidated by spectroscopic methods including extensive 1D- and 2D-NMR techniques. The cytotoxicity of gramniphenol K was evaluated against five human tumor cell lines, and it showed cytotoxicity against A549, SHSY5Y and MCF7 cells with IC50 values of 6.2, 7.5 and 4.7 μM, respectively.